'Till the whisper…You know…When you can't hear the words': Narrated Memory and the 'Fragmented' Body in Samuel Beckett's Late Drama. Issue 2 (September 2021) - Charalambous, Michelle
Abstract : Samuel Beckett's interest in the experience of memory and the central role the body plays in the re-experience of the past has been most evident since the time he composed Krapp's Last Tape (1958), one of his most famous memory plays where the body can actually 'touch' its voice of memory. In this context, the present article provides a close reading of two of Beckett's late works for the theatre, namely That Time (1976) and Ohio Impromptu (1981), where the author once again addresses the relationship between the body and memory. Unlike his earlier drama, however, in That Time and Ohio Impromptu Beckett creates a 'distance', as it were, between memory and the body on stage by presenting the former as a narrative and by reducing the latter to an isolated part or by restricting it to limited movements. Looking closely at this 'distance' in these late plays, the article underlines that the body does not lose its authority or remains passive in its re-experience of the past. Rather – the article argues – the body essentially plays a determining role in these stripped-down forms as is shown in its ability to 'interrupt' and somatically punctuate the fixity of the narrative form memory takes in these works.